Лінгвофольклористичні студії у другій половині ХХ - на початку ХХІ століть - Данилюк, Н. (Народна творчість та етнографія, 2007)
The article deals with the main achievements of the development of the Ukrainian, Russian and Polish linguistic folklore studies. In the article the notion ‘the language of folklore’ is defined.